Is Employee Performance Determined by Remuneration and Work Discipline? - Iedil, Iedil; Fajriah, Yana (International Business Management - Universitas Ciputra, 2024)
The aim of this research is to examine the effect of remuneration and work discipline on employee performance UIN Alauddin Makassar Rectorate. The sampling technique in this study used a Jenu sample because the population was limited to 50 people. The research results show that remunerationremuneration has a positive and insignificant effect on the performance of the employees of the Rectorate of UIN Alauddin Makassar. This can be interpreted as meaning that the lower the remuneration given, the employee performance continues to increase. Next, work disciplineThis research shows that there is a significant positive influence on the performance of the employees of the UIN Alauddin Makassar Rectorate. This can be interpreted as meaning that the higher the employee's work discipline value, the more performance will increase.